PENGARUH KEPEMILIKAN INSIDER DAN KEPEMILIKAN INSTITUSIONAL TERHADAP DIVIDEND PAYOUT RATIO DENGAN MEMPERGUNAKAN STRUKTUR MODAL SEBAGAI VARIABEL KONTROL PADA PERUSAHAAN YANG GO PUBLIC DI BURSA EFEK INDONESIA - Paulina, Sonti; Silalahi, Donalson (Jurnal Manajemen dan Bisnis, 2016)
This study aimed to examine the effect of ownership structure on dividend policy on companies that go public in Indonesia Stock Exchange in 2012-2013 with a sample of 54 companies. Data were obtained from the Indonesian Capital Market Directory (ICMD) and the Indonesia Stock Exchange website. There are two equations developed in this study. The first equation to examine the effect of the company's ownership structure on dividend policy. While in the second equation entered the control variables, namely the debt-to-equity ratio to test the consistency of the company's ownership structure influence on dividend policy. Techniques using multiple linear regression analysis and hypothesis testing statistical t and F statistics. Hypothesis test results indicate that the stock insider ownership variable significant negative effect on the company's dividend policy, while the institutional ownership variables significant negative effect on dividend policy. Taken together the ownership structure share a significant effect on the company's dividend policy which go public in Indonesia Stock Exchange. Adjusted R2 values after admission control variable increased from 0,053 to 0,044 be inferred variable debt to equity ratio is a variable that helps to explain the variation in the dividend policy of the company went public in Indonesia Stock Exchange.